WORK-FAMILY CONFLICT ACROSS THE LIFESPAN: FROM CHILDCARE TO ELDERCARE - Dilger, Kelly A. (My University, 2009)
Due to the recent trend that older workers are delaying retirement and that there is an increasing need for caring for the elderly, work-family conflict could be expected to expand into workers' preretirement years. The aim of this study was to examine work-family conflict (WFC) across the lifespan to determine if work-family conflict due to childcare demands experienced early in life is similar to the work-family conflict due to eldercare demands experienced later in life. Data for the study came from the sibling sample of the 1994 wave of the Wisconsin Longitudinal Study (WLS) of the University of Wisconsin-Madison. Participants completed a 1 hour telephone interview and were mailed a 20 page self-administered mail back questionnaire. Participants included in the analyses were divided into two subsamples where 1,096 men and women were identified as having childcare responsibilities and 300 men and women were identified as having eldercare responsibilities. A series of hierarchical multiple regressions and hierarchical moderated multiple regressions were used to test the hypotheses. The hypothesis examining the relationship between childcare demands and WFC was supported, but the hypothesis examining the relationship between eldercare demands and WFC was not. In addition, the hypotheses examining how WFC due to childcare demands (experienced early in life) is similar to WFC due to eldercare demands (experienced later in life) were not supported. Interpretations of these results, limitations of the study, and suggestions for future research are further discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Psychology Industrial/Organizational
Keywords: Caregivers Family relationships; Aging parents Care; Child care; Work and family United States